Synthesis and Biological Evaluation of Gastroprotective Polymer Conjugates of Aceclofenac - Mishra, Monika; Chawla, Viney; Chawla, Pooja A. (Current Organic Chemistry, 2024)
Nonsteroidal anti-inflammatory drugs account for a sizeable fraction of the drugs prescribed worldwide. If consumed for a long time, they can cause ulcers and lifethreatening side effects. Since the acidic group present in NSAIDs is mainly responsible for these side effects, the scientists try to synthesize polymer drug conjugates that avoid these side effects but still retain the potency of the parent drug. Macromolecular drug conjugates of aceclofenac were prepared by employing pectin, β cyclodextrin, deacetylated chitin (chitosan) and albumin (egg and bovine serum). The prepared conjugates were characterized and tested for their anti-inflammatory, antinociceptive and antiulcerogenic activity. Further experimentation was undertaken to analyze the behavior of compounds and their stability in hydrolytic conditions. Test compound A1, a pectin conjugate of aceclofenac, exhibited significant antinociceptive and anti-inflammatory activity with a significant decrease in ulcer index (4.45±0.24) as against aceclofenac (8.61±0.40) or vehicle (12.39±0.44) treated group. A novel and safer polymer drug conjugate of aceclofenac has been synthesized and evaluated.
Keywords: anti-inflammatory